Immune activation and immune aging in HIV infection. Issue 2 (March 2016) - Appay, Victor; Kelleher, Anthony D.
Abstract : Purpose of review: The development of serious non-AIDS-related pathologies typically associated with aging, and the premature immune aging that characterizes HIV-1-infected patients, even with suppressive antiretroviral therapy, have raised increasing concerns in recent years. Deciphering the causes of these phenomena is key for our understanding of HIV pathogenesis and for the clinical care of patients living with the virus. Recent findings: An important basis for the immune parallels between HIV infection and aging lies in the exhaustion of the lymphopoietic capacity of infected individuals, which eventually affects all compartments of the immune system. The alleged cause for these immune alterations, and the onset of age-related comorbidities, is the systemic chronic immune activation that is established in patients. However, there is a multiplicity of contributors to this immune activation. Summary: Our understanding of the precise link between immune activation and aging in HIV infection is complicated by the influence of coinfections and life style factors. Developing rational interventions to reduce the hyper-inflammatory status of HIV-1-infected patients requires a clearer delineation of the factors contributing to the increased levels of systemic immune activation.